2014
DOI: 10.1042/bst20130260
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal responses during early embryogenesis in maize

Abstract: Plant hormones have been shown to regulate key processes during embryogenesis in the model plant Arabidopsis thaliana, but the mechanisms that determine the peculiar embryo pattern formation of monocots are largely unknown. Using the auxin and cytokinin response markers DR5 and TCSv2 (two-component system, cytokinin-responsive promoter version #2), as well as the auxin efflux carrier protein PIN1a (PINFORMED1a), we have studied the hormonal response during early embryogenesis (zygote towards transition stage) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 23 publications
1
64
0
Order By: Relevance
“…ZmPIN1a , -b , -c are ubiquitously expressed but differentially modulated in maize vegetative and reproductive tissues and during kernel development. ZmPIN1 plays an important role during embryogenesis, where detectable hormone activity inside the developing maize embryo appears much later than in Arabidopsis (Forestan et al, 2010; Chen et al, 2014). In situ hybridization showed that ZmPIN1a localizes in the root apical meristem (RAM) and the calyptrogen, which is a specialized layer of meristematic cells that continuously generate replacements for the root cap cells that die during primary root growth.…”
Section: Pinsmentioning
confidence: 99%
“…ZmPIN1a , -b , -c are ubiquitously expressed but differentially modulated in maize vegetative and reproductive tissues and during kernel development. ZmPIN1 plays an important role during embryogenesis, where detectable hormone activity inside the developing maize embryo appears much later than in Arabidopsis (Forestan et al, 2010; Chen et al, 2014). In situ hybridization showed that ZmPIN1a localizes in the root apical meristem (RAM) and the calyptrogen, which is a specialized layer of meristematic cells that continuously generate replacements for the root cap cells that die during primary root growth.…”
Section: Pinsmentioning
confidence: 99%
“…This is also the point when cytokinin activity becomes clearly associated with the SAM, which as we discuss below is a key element in maintaining WUS expression (Zürcher et al, 2013). The association of cytokinin activity with the embryonic SAM also occurs in monocots, even though monocots differ from dicots in the cell division patterns that occur during embryogenesis (Chen et al, 2014). Maintenance of a stem cell population in the SAM thereafter relies on a non-cell-autonomous feedback loop involving WUS and the CLAVATA (CLV) signaling pathway ( Figure 5C).…”
Section: Auxin/cytokinin Interactions Above Ground Molecular Mechanismentioning
confidence: 99%
“…We therefore analyzed the expression of auxin biosynthesis, transport, and response genes, as shown in Figure 7 (Supplemental Data Set 3D; important gene families). In maize, the earliest ZmPIN1a localization was observed at 6 DAP at the adaxial side of the embryo proper (Chen et al, 2014). To identify potential PIN proteins that function at the earliest stage of embryo patterning, we analyzed the expression of all PIN family genes.…”
Section: The Role Of Auxin In Early Embryogenesis In Maizementioning
confidence: 99%